In situ macrophage reprogramming via micropatch engineering for safe and effective antitumor adoptive cell therapy - Yongkang Xu; Lei Cao; Yuyan Zhou; Wenhao Li; Han Lin; Yuan Yong; Jianlin Shi; Wencheng Wu (Science Bulletin, 2026)

Nonlinear dynamic behavior of deep-sea mining lifting riser system under vessel-vehicle linkage - Lin Huang; Honglu Gu; Shuqing Wang; Wencheng Liu; Jiayu Zhang; Yuanyuan Liu (Ocean Engineering, 2026)

Void-fraction-based classification of plunging wave impacts on a surface-piercing column - Wencheng Wu; Longfei Xiao; Lin Yuan; Handi Wei; Yufeng Kou; Hongrui Guo (Coastal Engineering, 2026)

A multi-objective optimization framework for the global configuration of vertical transportation system in deep-sea mining - Xiaomin Li; Dayue Lin; Mingqiang Xu; Wencheng Liu; Honglu Gu (Ocean Engineering, 2026)

Real-time simulation for deep-sea mining system with sea trial validation - Lin Huang; Shuqing Wang; Wencheng Liu; Yuankun Sun; Ying Li; Xuewu Hong; Mingqiang Xu; Lianjin Jiang; Fang Xu; Yuanhe Li; Hai Wu; Chi Zhan (Ocean Engineering, 2025)

Evidence for vertical transmission of avian reovirus in chickens - Li Chen; Lijuan Yin; Li Li; Zhiqiang Wu; Jialin Yang; Shenghua Yang; Xuesong Li; Qingfeng Zhou; Zhanxin Wang; Wencheng Lin (Veterinary Microbiology, 2025)

Corrigendum to “Critical role for heat shock protein 70 in viral replication of ALV-J via interaction with gp37 and P32,” [Vet. Microbiol. 303 (2025) 110436] - Kensi Zhu; Yanling Pang; Zhihong Luo; Hanyue Zhang; Shuang Tang; Jinjie Liang; Yuecheng Long; Wencheng Lin (Veterinary Microbiology, 2025)

Application of cold plasma for rice bran preservation: Effects on stability and quality - Wencheng Yang; Huanhuan Ma; Huanling Lan; Wenxia Liao; Xueyuan Lin; Chang Li (Innovative Food Science & Emerging Technologies, 2025)

Evolved size-specific dose estimates for patient-specific organ doses from chest CT scans based on hybrid patient size vectors - Wencheng Shao; Ke Yang; Lizhi Lou; Xin Lin; Liangyong Qu; Weihai Zhuo; Haikuan Liu (Physical and Engineering Sciences in Medicine, 2025)

Critical role for heat shock protein 70 in viral replication of ALV-J via interaction with gp37 and P32 - Kensi Zhu; Yanling Pang; Zhihong Luo; Hanyue Zhang; Shuang Tang; Jinjie Liang; Yuecheng Long; Wencheng Lin (Veterinary Microbiology, 2025)

Exploring the gelation potentials of chicken heart batter: From by-product to product - Mingxia Li; Langye Jiang; Zonglin Guo; Jie Lin; Hua Zheng; Wencheng Lin; Haili Zeng; Jiankun Wu; Hongtao Lei; Shaozong Wu (Food Chemistry, 2025)

Real-Time Prediction of the Dynamic Spatial Configuration of Umbilical Cables Based on Monitoring Data During Deep-Sea In-Situ Mining - Chaojun Huang; Shuqing Wang; Jiancheng Liu; Lei Li; Wencheng Liu; Lin Huang; Zhihao Yu; Wen Shen; Yuankun Sun; Yu Liu; Yuanyuan Liu (Journal of Marine Science and Engineering, 2025)
Prediction of the spatial configuration of the umbilical cable during deep-sea mining in-situ tests is of great significance because dynamic change may cause the umbilical cable to touch the ground or overturn the mining vehicle. In the present paper, a real-time prediction method for the dynamic spatial configuration of the umbilical cable during the deep-sea mining process is proposed. At first, the environmental information, position and motion of the vessel–umbilical cable–mining system were collected by sensors arranged at different locations. Then, the data were converted and transformed to the local vessel coordinate system. After that, the commercial software OrcaFlex was employed to conduct real-time simulation, in which the spatial configuration of the umbilical cable was predicted by the lumped mass method. Furthermore, the proposed real-time simulation method was employed in a sea trial test of deep-sea mining in an area with a water depth of 1100 m. Comparing the prediction results with the trajectory of the USBL beacon obtained from the monitoring data, the maximum distance of some specific points was close to 5 m, and most of them were less than 3 m. Meanwhile, it could also give the dynamic responses of the deep-sea mining system. For example, the maximum top tension of the umbilical cable was less than 15 kN, which could be used to evaluate the health condition of the system. During the sea trial test, the proposed method played an important role in ensuring the safety of the umbilical cable during wide-range movement of the mining vehicle. With characteristics of good real-time performance, accurate prediction, high reliability and stability, the proposed method could enhance the confidence of engineers for on-site operation as a powerful digital tool for visualization of the subsea working state.

Three-dimensional analysis of China's fisheries insurance policy: A tool-direction-subject perspective - Wencheng Yu; Benshuo Zhu; Kangkang Lin (Marine Policy, 2024)

Novel variant infectious bursal disease virus diminishes FAdV-4 vaccination and enhances pathogenicity of FAdV-4 - Zhishan Liang; Mei Leng; Jiamin Lian; Yazheng Chen; Qi Wu; Feng Chen; Zhanxin Wang; Wencheng Lin (Veterinary Microbiology, 2024)

Dynamic multicolor luminescent anti-counterfeiting based on spiropyran-engineered gold nanoclusters - Lin Wang; Wencheng Zhong; Wenxing Gao; Wenfeng Liu; Li Shang (Chemical Engineering Journal, 2024)

The attenuated live vaccine strain W2512 provides protection against novel variant infectious bursal disease virus - Mei Leng; Xiaomeng Bian; Yazheng Chen; Zhishan Liang; Jiamin Lian; Meng Chen; Feng Chen; Zhanxin Wang; Wencheng Lin (Archives of Virology, 2023)

gga-miR-20b-5p inhibits infectious bursal disease virus replication via targeting Netrin 4 - Zixian Chen; Mei Leng; Zhishan Liang; Puduo Zhu; Sheng Chen; Qingmei Xie; Feng Chen; Wencheng Lin (Veterinary Microbiology, 2023)

Retrospective detection and phylogenetic analysis of pseudorabies virus in dogs in China - Lu Tu; Jiamin Lian; Yanling Pang; Cun Liu; Shangjin Cui; Wencheng Lin (Archives of Virology, 2021)

Epidemiology, molecular characterization, and recombination analysis of chicken anemia virus in Guangdong province, China - Chen Tan; Zhanxin Wang; Xiaoya Lei; Junpeng Lu; Zhuanqiang Yan; Jianping Qin; Feng Chen; Qingmei Xie; Wencheng Lin (Archives of Virology, 2020)

Knockout of Atg5 inhibits proliferation and promotes apoptosis of DF-1 cells - Zhihong Liao; Zhenkai Dai; Chenyu Cai; Xinheng Zhang; Aijun Li; Huanmin Zhang; Yiming Yan; Wencheng Lin; Yu Wu; Hongxin Li; Haiyun Li; Qingmei Xie (In Vitro Cellular & Developmental Biology - Animal, 2019)

Assessing the efficacy of a live vaccine against avian encephalomyelitis virus - Wencheng Lin; Piaopiao Lu; Aijun Li; Yu Wu; Hongxin Li; Feng Chen; Jingyun Ma; Qingmei Xie (Archives of Virology, 2018)

Sharp and laterally constrained multitrace impedance inversion based on blocky coordinate descent - Yaojun Wang; Wencheng Lin; San Cheng; Bin She; Guangmin Hu; Wei Liu (Acta Geophysica, 2018)

Molecular epidemiology of J-subgroup avian leukosis virus isolated from meat-type chickens in southern China between 2013 and 2014 - Wencheng Lin; Xinjian Li; Zhenkai Dai; Xinheng Zhang; Shuang Chang; Peng Zhao; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

Isolation, identification and evolution analysis of a novel subgroup of avian leukosis virus isolated from a local Chinese yellow broiler in South China - Xinjian Li; Wencheng Lin; Shuang Chang; Peng Zhao; Xinheng Zhang; Yang Liu; Weiguo Chen; Baohong Li; Dingming Shu; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

Critical role of eukaryotic elongation factor 1 alpha 1 (EEF1A1) in avian reovirus sigma-C-induced apoptosis and inhibition of viral growth - Zhiqiang Zhang; Wencheng Lin; Xiaoqi Li; Hong Cao; Yongqiang Wang; Shijun J. Zheng (Archives of Virology, 2015)

Assessment and zoning of eco-environmental sensitivity for a typical developing province in China - Xiaoyan Dai; Zhuo Li; Shouyi Lin; Wencheng Xu (Stochastic Environmental Research and Risk Assessment, 2012)

A real-time PCR to detect and analyze virulent EMCV loads in sows and piglets - Zhao Wang; Yebing Liu; Wencheng Lin; Shangjin Cui (Molecular Biology Reports, 2012)

Phylogeny and evolution of porcine teschovirus 8 isolated from pigs in China with reproductive failure - Wencheng Lin; Shangjin Cui; Roland Zell (Archives of Virology, 2012)

A potentially novel reovirus isolated from swine in northeastern China in 2007 - Chaofan Zhang; Licheng Liu; Pengzhi Wang; Shanshan Liu; Wencheng Lin; Feng Hu; Weili Wu; Weijun Chen; Shangjin Cui (Virus Genes, 2011)